Adoption and use of Facebook among Malaysian political representatives - Nurshuhada Mohammed, Rosyidah Muhamad, Siti Aisyah Saat, Rahaya Mat Jamin, (Opción, 2019)
The study evaluates the extent Members of Parliament (MPs’) effort of political communication with their constituents might contribute to deliberative democracy. The paper finds that MPs’ approaches to Facebook are conditioned by specific personal aims for a strategic marketing channel rather than a communication channel with their constituents. In conclusion, MPs were able to legitimize their roles by demonstrating their services as parliamentarians or representatives